Representasi Relasi Kuasa melalui Analisis Wacana Multimodal: Studi Kasus Sampul Majalah Tempo Edisi ‘KUHAP!’ - Daris Sabrina Az Zahra (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2026)
Language in the media is rarely neutral, particularly on magazine covers, which frequently serve as a medium for social critique. This study is motivated by the polemic surrounding the revision of the Indonesian Criminal Procedure Code (KUHAP), which has raised public concerns regarding the restriction of civil liberties. This research aims to: (1) describe the construction of verbal, visual, and spatial elements on the cover of Tempo Magazine's 'KUHAP! Lalu Ditangkap!' edition; (2) identify the interaction among these multimodal elements in constructing discursive meaning; and (3) uncover the representation of unequal power relations through these multimodal features. This study employed a qualitative descriptive method, integrating Norman Fairclough’s Critical Discourse Analysis (CDA) with Gunther Kress and Theo van Leeuwen’s Multimodal Discourse Analysis (MDA). The results indicate that the verbal mode utilizes concise and satirical diction. Meanwhile, the visual mode illustrates the dominance of the authorities over the KUHAP book, which is depicted as a dog on a leash, a metaphor suggesting that the law is entirely under the control of the law enforcement apparatus. The interconnectedness of these modes effectively constructs and highlights an imbalance in power relations. These findings confirm that mass media cover design operates as a social practice capable of implicitly influencing public perception regarding the power dynamics among the law, the state apparatus, and civilians.